Analysis of HLA class II genes in Hashimoto's thyroiditis reveals differences compared to Graves’ disease - Zeitlin, A A; Heward, J M; Newby, P R; Carr-Smith, J D; Franklyn, J A; Gough, S C L; Simmonds, M J (Genes and immunity, 2008)
Graves’ disease (GD) and Hashimoto's thyroiditis (HT) represent the commonest forms of autoimmune thyroid disease (AITD) each presenting with distinct clinical features. Progress has been made in determining association of HLA class II DRB1, DQB1 and DQA1 loci with GD demonstrating a predisposing effect for DR3 (DRB1 * 03-DQB1 * 02-DQA1 * 05) and a protective effect for DR7 (DRB1 * 07-DQB1 * 02-DQA1 * 02). Small data sets have hindered progress in determining HLA class II associations with HT. The aim of this study was to investigate DRB1-DQB1-DQA1 in the largest UK Caucasian HT case control cohort to date comprising 640 HT patients and 621 controls. A strong association between HT and DR4 (DRB1 * 04-DQB1 * 03-DQA1 * 03) was detected ( P =6.79 × 10 −7 , OR=1.98 (95% CI=1.51–2.59)); however, only borderline association of DR3 was found ( P =0.050). Protective effects were also detected for DR13 (DRB1 * 13-DQB1 * 06-DQA1 * 01) ( P =0.001, OR=0.61 (95% CI=0.45–0.83)) and DR7 ( P =0.013, OR=0.70 (95% CI=0.53–0.93)). Analysis of our unique cohort of subjects with well characterized AITD has demonstrated clear differences in association within the HLA class II region between HT and GD. Although HT and GD share a number of common genetic markers this study supports the suggestion that differences in HLA class II genotype may, in part, contribute to the different immunopathological processes and clinical presentation of these related diseases.